Moving beyond reflection in a hall of mirrors: developing critical reflective capacity in teachers and teacher educators. Issue 3 (4th May 2019) - Fox, Rebecca K.; Dodman, Stephanie; Holincheck, Nancy
ABSTRACT: Using reflection to merely affirm existing beliefs rather than engaging in confrontation and examination of beliefs is like reflecting in a hall of mirrors. This study explores the process of critical reflective development of practicing teachers through program reflections written to prompts during master's-level coursework, seeking to understand: How does critical reflective capacity develop and change in practicing teachers enrolled in advanced coursework in an M.Ed. program? Researchers used a three-level reflective practice pyramid as a frame for examining teachers' reflective writings. Specifically, 103 reflections from 26 PK-12 teachers were available for analysis. Where finding a clear trajectory in teacher's reflective development was an anticipated outcome in which teachers would progress from the technical to contextual to dialectical levels of reflection, findings did not indicate such linear development for most teachers. As faculty analyzed the data, they engaged in critical reflection, also questioning purposes and program outcomes. This paper reports on both our study's findings in response to the research question and on the results of faculty reflective engagement. Results reinforce the understanding that reflection is an individual journey for teachers and faculty alike; results also highlight the importance for engagement in critical reflection for both teachers and teacher educators.